A SURVEY ON PRACTICE OF INSULIN THERAPY AMONG HEALTHCARE PROVIDERS - Salleh, Mohd Fauzan; Jailani, Khairunnisa’; Tong, Chin Voon (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Effective insulin therapy is crucial in the management of type 2 diabetes mellitus (T2DM). While initiation and intensification are commonly practiced, insulin de-intensification—reducing or simplifying insulin regimens—remains less well described in clinical settings. METHODOLOGY This is a retrospective review of a cross-sectional survey conducted among healthcare providers who attended the “Insulin Workshop for Healthcare Professionals 2024” at Hospital Putrajaya on November 14, 2024. All participants who completed the self-administered questionnaire were included. Data on professional background, insulin therapy practices, and pre- and post-workshop knowledge scores were analyzed. RESULT A total of 167 respondents participated in the survey, with 43% from hospitals and 57% from primary care. Most respondents had over 10 years of working experience (51.5%), followed by 5–10 years (38.3%), and less than 5 years (10.2%). The majority reported initiating insulin in outpatient settings (87.4%), intensifying therapy when appropriate (97%), and practicing insulin de-intensification (90%) in their practice. Additionally, 73.7% stopped insulin in selected patients. The mean knowledge score improved from 76.77% pre-test to 89.39% post-test following the workshop. CONCLUSION Insulin initiation and intensification are commonly practiced among local healthcare providers. A high proportion is also aware about insulin de-intensification and reported practicing insulin de-intensification and discontinuation, suggesting growing awareness of individualized diabetes care. The significant improvement in post-test scores highlights the effectiveness of structured educational interventions in enhancing knowledge related to insulin therapy and T2DM management. Despite limitations of the retrospective, self-reported design and lack of sample generalizability, these findings support the value of ongoing training to promote safe and evidence-based insulin use and promote safe de-intensification in clinical practice.